Manajemen Analisis Komparatif Indikator Financial Distress Berbasis Arus Kas: Studi Kasus PT GoTo Gojek Tokopedia Tbk dan PT Blue Bird Tbk Pasca-Tren AI 2025 - Ni Made Meliani Andari; Kharizsa Imamara; Ida Bagus Gede Dananjaya (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The integration of Artificial Intelligence (AI) in 2025 has become one of the main pillars in improving operational efficiency in transportation service companies. This study aims to comparatively analyze the potential financial distress of PT GoTo Gojek Tokopedia Tbk as a digital company and PT Blue Bird Tbk as a conventional transportation company. The research employed a quantitative descriptive method using the Operating Cash Flow Ratio (AKO) analysis approach. The data were obtained from consolidated financial statements for the third quarter period from 2023 to 2025. The results indicate that GOTO consistently remained in the financial distress zone with negative ratio values of -0.34, -0.11, and -0.01. However, the implementation of AI technology helped improve operational efficiency, resulting in significant annual ratio improvements. On the other hand, BIRD demonstrated relatively stable and positive cash flow conditions, although in 2025 the company experienced a decline in liquidity with a ratio value of 0.69, which was below the ideal standard of 1.0. This study concludes that the AI trend in 2025 contributed to reducing operational inefficiencies in transportation companies, but it has not fundamentally eliminated the risk of financial distress in digital companies.